Copper-Boosting Compounds: a Novel Concept for Antimycobacterial Drug Discovery - Speer, Alexander (American Society for Microbiology, 2013)
We and others recently identified copper resistance as important for virulence of Mycobacterium tuberculosis. Here, we introduce a high-throughput screening assay for agents that induce a copper hypersensitivity phenotype in M. tuberculosis and demonstrate that such copper-boosting compounds are effective against replicating and nonreplicating M. tuberculosis strains.